5 Porter Force Analysis in Cattle and Sheep Integrator Business (Case Study at PT Sapi Domba Indonesia) - Arifwandi, Setiana; Sitorus, Jusuf; Sutrisno, Sutrisno; Syah, Tantri Yanuar Rahmat; Sunaryadi, Ketut; Hamdi, Edi (Budapest International Research and Critics University, 2022)
The increasing need for meat for some people is a necessity and makes meat consumption increase drastically. This is inseparable from the increasing number of restaurants and restaurants in the Special Region of Yogyakarta. Seeing this opportunity, a beef and lamb integrator company is trying to find out the competitive advantage in its company. This research is descriptive qualitative research, where in this study using research data from interviews and literature and data and using 5 porter analysis measurements. The findings in this study show that porter's Five Forces analysis on the parameters of Threat of Entry, Industry Rivalry, Bargaining Power of Buyers, Bargaining Power of Supplier, Substitute Competition with an average weight of 2.06. From the analysis of Porter's Five Forces above quantitative results in the range of 1.67 – 2.33, it shows that the competitive advantage of PT Sapi Domba Istimewa is in low pressure. The limitations in this study are limited to the analysis of competitive advantages only. Meanwhile, in the next study, it is recommended that you can add or complement other supporting data such as SWOT, QSPM analysis and expand the scope of research not only in the Yogyakarta Special Region Area.